Assessment of Nutritional Status, Digestion and Absorption, and Quality of Life in Patients with Locally Advanced Pancreatic Cancer - J. E. Witvliet-van Nierop; C. M. Lochtenberg-Potjes; N. J. Wierdsma; H. J. Scheffer; G. Kazemier; K. Ottens-Oussoren; M. R. Meijerink; M. A. E. de van der Schueren (Gastroenterology Research and Practice)
Background and Aim. To provide a comprehensive quantitative assessment of nutritional status, digestion and absorption, and quality of life (QoL) in patients with locally advanced pancreatic cancer (LAPC). Methods. Sixteen patients with LAPC were prospectively assessed for weight loss (WL), body mass index (BMI), fat-free mass index (FFMI), handgrip strength (HGS), dietary macronutrient intake, serum vitamin levels, resting and total energy expenditure (REE and TEE, indirect calorimetry), intestinal absorption capacity and fecal losses (bomb calorimetry), exocrine pancreatic function (fecal elastase-1 (FE1)), and gastrointestinal quality of life (GIQLI). Results. Two patients had a low BMI, 10 patients had WL > 10%/6 months, 8 patients had a FFMI < P10, and 8 patients had a HGS < P10. Measured REE was 33% higher (P=0.002) than predicted REE. TEE was significantly higher than daily energy intake (P=0.047). Malabsorption (<85%) of energy, fat, protein, and carbohydrates was observed in, respectively, 9, 8, 12, and 10 patients. FE1 levels were low (<200 μg/g) in 13 patients. Total QoL scored 71% (ample satisfactory). Conclusion. Patients with LAPC have a severely impaired nutritional status, most likely as a result of an increased REE and malabsorption due to exocrine pancreatic insufficiency. The trial is registered with PANFIRE clinicaltrials.gov NCT01939665.